Analysis of ripening-related gene expression in papaya using an Arabidopsis-based microarray - Fabi, João Paulo; Seymour, Graham B.; Graham, Neil S.; Broadley, Martin R.; May, Sean; Lajolo, Franco Maria; Cordenunsi, Beatriz Rosana; Oliveira do Nascimento, João Roberto (BioMed Central, 2012)
Background